Synthesis, structure and magnetism of a new ionic pentanuclear iron cluster. Issue 7 (29th June 2020) - Deng, Qianjun; Wang, Jiming; Li, Guangzhao; Zhang, Shuhua
Abstract : A new ionic pentanuclear Fe III cluster was synthesized using microvial synthesis methods. Magnetic studies reveal that the complex displays dominant antiferromagnetic intracluster interactions between Fe III ions through μ3 ‐oxide bridges. Abstract : A new ionic pentanuclear Fe III cluster, namely, triethylazanium tetrakis(μ2 ‐5‐amino‐1, 2, 3, 4‐tetrazolido)tetrakis(μ3 ‐4‐chloro‐2‐{[(1 H ‐tetrazol‐1‐id‐5‐yl)imino]methyl}phenolato)di‐μ3 ‐oxido‐pentairon(III) acetonitrile monosolvate monohydrate, (C6 H16 N)[Fe5 (C8 H4 ClN5 O)4 (CH2 N5 )4 O2 ]·CH3 CN·H2 O, was synthesized using microvial synthesis methods and characterized by elemental analysis, FT–IR spectroscopy, single‐crystal X‐ray diffraction and thermogravimetric analysis. Magnetic studies reveal that the complex displays dominant antiferromagnetic intracluster interactions between the Fe III ions through the μ3 ‐oxide bridges.